EVALUASI KEBIJAKAN SISTEM ZONASI PPDB: ANTARA TUJUAN PEMERATAAN DAN REALITA KESENJANGAN MUTU SEKOLAH - Lukman El Hakim; Muhammad Melvin Naufal (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The zoning-based New Student Admissions Policy (PPDB) was designed by the government as a concrete effort to ensure equal access, accelerate the distribution of educational quality, and eliminate the labels of